Navigating the future of higher education. harnessing the potential of hybrid, hyflex and phygital learning models. - Saad, Wan Zuhainis (UCSI PRESS, 2024)
The COVID-19 infection has increased online education's emergence. This approach allows for a flexible blend of real and virtual experiences, which are not merely technological tools but strategic adaptations to socio-technological changes.